2013
DOI: 10.1002/glia.22495
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the cell adhesion adaptor protein vinculin disturbs the localization of GFAP in Bergmann glial cells

Abstract: Astrocytes operate in close spatial relationship to other cells including neurons. Structural interaction is controlled by a dynamic interplay between actin-based cell motility and contact formation via cell-cell and cell-extracellular matrix adhesions. A central player in the control of cell adhesion is the cytoskeletal adaptor protein Vinculin. Incorporation of Vinculin affects mechanical properties and turnover of cell adhesion sites. To study the in vivo function of Vinculin in astrocytes, a mouse line wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Neural cells generated from HD-affected hESC demonstrated a vast network of cytoskeletal protein alteration and dysregulation, presumably leading to an overall reduction in cell motility and intracellular trafficking. Decreases in the cytoskeletal proteins radixin (RDX), myosin light chain 6 (MYL6) and IQ motif-containing GTPase activating protein 1 (IQGAP1) all suggested that HD neuronal cells were undergoing severe disruptions in axonal transport. Talin-1, vinculin, and α-actinin are known to be intimately involved in the creation and maintenance of focal adhesions, the anchoring of cytoskeleton to the extracellular matrix (ECM) and critical for cell motility/migration, as well as response to the ECM environment. Reductions of profilin1 is associated with impaired formation of focal adhesions.…”
Section: Resultsmentioning
confidence: 99%
“…Neural cells generated from HD-affected hESC demonstrated a vast network of cytoskeletal protein alteration and dysregulation, presumably leading to an overall reduction in cell motility and intracellular trafficking. Decreases in the cytoskeletal proteins radixin (RDX), myosin light chain 6 (MYL6) and IQ motif-containing GTPase activating protein 1 (IQGAP1) all suggested that HD neuronal cells were undergoing severe disruptions in axonal transport. Talin-1, vinculin, and α-actinin are known to be intimately involved in the creation and maintenance of focal adhesions, the anchoring of cytoskeleton to the extracellular matrix (ECM) and critical for cell motility/migration, as well as response to the ECM environment. Reductions of profilin1 is associated with impaired formation of focal adhesions.…”
Section: Resultsmentioning
confidence: 99%
“…About 45 μm thick vibratome sections were prepared and stained for the pan‐astrocyte marker 3‐phosphoglycerate dehydrogenase (3PGDH; Yamasaki et al, 2001) using a guinea pig anti‐3PGDH antibody (1:200, Frontier Institute, Ishikari, Hokkaido, Japan) and a donkey anti guinea pig CF633 (1:250, Sigma‐Aldrich) in combination with a goat anti‐GFP (Biotin conjugated) antibody (1:200, Rockland Immunochemicals, Pottstown, PA) and Streptavidin‐Cy2 (1:500, Dianova, Hamburg, Germany). The staining protocol was previously described in detail (Winkler et al, 2013). Sections were mounted in ImmunoSelect Antifading Mounting Medium DAPI (Dianova).…”
Section: Methodsmentioning
confidence: 99%
“…In cell culture, the actin cytoskeleton directly governs the localization of aquaporin-4 (Nicchia et al, 2008 ). Deleting the focal adhesion adapter protein vinculin in Bergmann glia disturbs the GFAP distribution in endfeet but has no obvious effect on neurovascular functions (Winkler et al, 2013 ).…”
Section: Stars With Sensitive Feetmentioning
confidence: 99%